Legal Framework for Soil Erosion Management in Housing Development: Reforming Malaysia’s Planning Law - Md Dahlan, Nuarrual Hilal (Zes Rokman Resources (2131022-P), 2025)
Many landslides occurring in housing areas in Malaysia have intrigued and shocked the Malaysian public. These disasters have caused massive damage to property and losses of life. It is a trite fact that, in Malaysia, soil problems have negatively impacted the residents' lives and property. The most significant soil problem disaster in Malaysia was the collapse of Highland Towers in 1993. This disaster caused pecuniary and non-pecuniary losses to the residents of the buildings. The question is, what can be learned so far from these land-related catastrophes? The main objective of this writing is to analyse the legal provisions in the planning law that have bearings on soil problems and soil erosions in housing areas. This writing aims to explore the weaknesses in the planning law and its implementation to provide preventive and curative legal measures against soil problems, soil erosions, and their consequences in housing development areas. This writing proposes a new perspective on planning legal ideas governing soil fitness in housing development areas. Qualitative social and legal research methodologies were used to study the facts and issues. The subjects of this research involve many housing development areas that face soil problems in Malaysia. It follows that the outcomes of this writing and the proposed legal reforms relating to planning law in housing areas can be improved to face the soil problems and protect the rights of the house residents